Faculty Workload Issues Connected to Undergraduate Research. Issue 169 (March 2015) - Free, Rhona; Griffith, Suzanne; Spellman, Bill
Abstract : This chapter delineates the consortial activities of the Council of Public Liberal Arts Colleges (COPLAC) to explore models of undergraduate research and to address the impact of undergraduate research on faculty workload. The significant progress made on the member campus of the University of Wisconsin‐Superior over the last 10 years is highlighted as an example of the fortuitous impact of several concurrent factors in advancing undergraduate research.